Impedance and AC Conductivity of GdCr1−xCoxO3 (x = 0, 0.33, 0.5, 0.67 and 1) Perovskites. Issue 12 (1st September 2014) - Pecovska‐Gjorgjevich, Margareta; Aleksovska, Slobotka; Marinšek, Marjan; Dimitrovska‐Lazova, Sandra
Abstract : Perovskite series GdCr1− x Co x O3 ( x = 0, 0.33, 0.5, 0.67 and 1) was obtained using a solution combustion method. The powder XRD was used for identification and structural characterization of the obtained perovskites. All compounds crystallize within the space group Pnma . The morphology of samples was studied using SEM. The impedance and AC conductivity of GdCr1− x Co x O3 were studied using impedance spectroscopy in a frequency range from 10 Hz to 10 MHz and in temperature interval 297–337 K. Changes in electric modulus and DC conductivity, with increasing of the value of x in the structures, were observed. The AC conductivity obeyed the universal power law, σ(ω) = σ(0) + A ω n and revealed semiconductor behavior. The calculated activation energies of existing processes varied with the cobalt content and applied frequency. The impedance spectra showed non‐Debye behavior with a distribution of relaxation times for relaxation and conductive processes. The conduction mechanism for pure orthochromite and orthocobaltite was defined and two types of conduction were observed in the investigated temperature range for the complex perovskites. In order to explain the results, an equivalent circuit with fitted values of circuit components was proposed.